IMPACT OF SOCIAL NETWORKS USAGE ON POLITICAL INFORMING AND POLITICAL KNOWLEDGE OF STUDENTS IN SERBIA - Obradović, Neven D. (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2021)
The subject of this paper is the impact of social media on political informing and political knowledge of students in Serbia. Based on the premise that social media users can independently create their own information and cognitive environment, our theoretical starting point is the uses and gratification theory, which is often applied in the current research on the impact of social media on different forms of political participation. The main goal of the empirical research is to determine whether the use of social media based on satisfying the daily information, communication and entertainment needs brings about changes in the informing and political knowledge of Serbian students. Therefore, the main hypothesis of the research is – the use of social media based on gratifying the needs for information, communication and entertainment leads to better informing and knowledge about politics among students in Serbia. The research sample (N=554) consisted of students aged 19-24 from the Republic of Serbia. In addition, the respondents were the students from the three largest universities in the Republic of Serbia (the University of Belgrade, the University of Novi Sad and the University of Niš). The research findings indicated that the use of social media for the purpose of meeting users’ personal needs for general information, communication and entertainment does not lead to a better informing and knowledge about politics among students in Serbia.
Keywords: social networks sites; political knowledge; uses and gratification theory; young people; Serbia